Integrasi Hukum Islam dan Hukum Positif dalam Pemanfaatan dan Pengelolaan Rumput Laut di Kabupaten Bulukumba - Amanda, Serli; Safriani, Andi; Kahfi, Ashabul (Universitas Islam Negeri Alauddin Makassar, 2024)
This research presents two problem formulation items, namely: First, How is the role of the local government in the utilisation and management of seaweed in Bonto Bahari sub-district, Bulukumba regency? Second, How is the difference between the views of Islamic Law and Law No. 1 of 2014 in the context of management and utilisation of seaweed in Bonto Bahari sub-district? This type of research is a qualitative research method using two data collection methods, namely primary which is through observation, interviews, and documentation and secondly secondary, namely literature review through books, thesis journals, research reports and internet sites related to the author's title. The results of this study show two main things, namely: The role of the Government in the utilisation and management of seaweed in Bonto Bahari Subdistrict has been successfully implemented properly, namely first informing the community regarding the limits of seaweed distribution and the community who wants to manage the grass first notifying the location request to the government in order to obtain maximum seaweed yields. Secondly, Islamic teachings teach humans to utilise natural resources, especially marine resources, properly and wisely as explained in (Q.S An-Nahl Verse 14). Meanwhile, Law No. 1 of 2014 concerning seaweed management explains the management and utilisation of seaweed. Research Implications, It is hoped that the government will pay more attention to the level of community enthusiasm by encouraging the development of small and medium enterprises by developing existing resources and it is hoped that related agencies will pay more attention to MSMEs to manage processed seaweed into food, cosmetics, and others. With this, it can make the community's economy increase, because they can manage their seafood not only until the raw sales process but make high-value products that are easily marketed.